Effect Of Value Of Resistance Announcement To Thd In Electrical System Faculty Of Engineering University Udayana Denpasar - Janardana, I. G. N.; Arta Wijaya, I W; Karnata Mataram, I. N. (Journal of Electrical, Electronics and Informatics, 2018)
AC (Air Conditioner), TV, lamp, LCD and others are categorized as nonlinear load generating harmonics. The high content of harmonics has a negative impact on the quality of electrical power. The result of measurement of THD (Total Harmonic Distortion) current at 9 ohm ground resistance value at phase R = 9,8%, phase S = 11,0%, phase T = 7,5% exceed from standard value IEEE 519 Year 2014 equal to ? 5 , 0%, THD measurement of phase voltage R = 1.4%, phase S = 1.2%, phase T = 1.3%, meet the maximum THDv standard of ? 5%. To overcome this problem, it was observed the effect of the value of ground resistance to THDi and THDv on the electrical system of the College of Engineering Faculty of Denpasar. This method of analysis with ETAP software simulation. With grounding system ? 3 ohm only effect on current THD only with decreasing value of THDi become: phasa R = 4,2%, phase S = 5% and phase T = 4,3%, meaning with grounding system ? 3 ohm THD current fulfill IEEE 519 - 2014 standard <5%. while THD voltage has no effect (THD value of fixed voltage). Several studies have suggested that THD repair can be done by filter installation. However in this study the installation of grounding system ? 3 ohms can reduce the value of current THD.